Experimental and numerical study on joint-free bridges with steel or gfrp-reinforced ecc link slab subjected to static loading. (11th April 2022) - Chu, K.; Hossain, K.M.A.; Lachemi, M.
Highlights: Engineered Cementitious Composite link slab Joint-free bridges under static load. Effect of Glass Fibre Reinforced Polymer vs steel reinforced link slab on bridge. Analytical, experimental and finite element load capacities of link slab & bridge. Parametric finite element study on influence of link slab material properties. Abstract: Engineered Cementitious Composite (ECC) and Glass Fiber-Reinforced Polymers (GFRP) have shown substantial durability benefits compared with conventional steel-reinforced concrete. This makes ECC and GFRP ideal materials for construction of durable bridge deck link slabs routinely subjected to extreme weather/environmental conditions. This paper presents experimental results of a two-span joint-free bridge with GFRP-reinforced ECC link slab compared with its companion steel reinforced counterpart. Furthermore, finite element (FE) models of the joint-free bridges were developed and their performance validated based on experimental results using ABAQUS software. FE models were then used to conduct parametric study to investigate influence of various material properties on link slab stiffness, girder rotational capacity and failure modes. Experimental results showed that the use of low-modulus GFRP bars helped to improve bending flexibility and strain distribution in the link slab. Crack development and width control were also enhanced by the use of GFRP bar reinforced ECC link slab. As per the parametric study, greater link slab stiffness and tensile capacity resulted in lower girder end rotation at any given load. Analytical models were found to be good in predicting load capacities of steel/GFRP reinforced bridges with ECC link slabs.